(untitled) (Development Service Industry Management, 2025)
The article examines the conceptual foundations for ensuring energy security as one of the key strategic priorities of modern public policy in the context of globalization challenges, climate change, energy crises, and increasing geopolitical tensions. The purpose of the study is to substantiate the conceptual framework for ensuring energy security under conditions of global transformations, taking into account geopolitical, economic, environmental, social, technological, and institutional-regulatory challenges. The study presents a comprehensive analysis of definitions and approaches to interpreting the essence of energy security, considering the multifaceted nature of this concept. It is substantiated that energy security is not limited solely to the stability of energy supply but also encompasses institutional regulation, source diversification, infrastructure reliability, energy efficiency, and environmental balance. Key determinants of energy security are analyzed, including those highlighted in the works of both foreign and Ukrainian scholars, which allowed for identifying the interdisciplinary nature of this category. It is revealed that ensuring energy security is closely linked to the presence of a resilient and adaptive energy system capable of operating effectively under destabilizing conditions, particularly in the face of external political and economic shocks. The growing role of innovation, digital technologies, and renewable energy sources in strengthening the systemic stability of the energy sector is emphasized. The analysis of influencing factors made it possible to identify the most critical vulnerability zones of energy systems at both global and national levels, including geopolitical dependence on unstable regions, an unstable investment climate, technological backwardness of infrastructure, a low level of energy efficiency, and institutional gaps in regulation. It is substantiated that overcoming these challenges requires the development of a comprehensive multi-level energy security policy with a focus on sustainable development, inclusivity, and international cooperation.